Enhanced hydrogen evolution activity over microwave-assisted functionalized 3D structured graphene anchoring FeP nanoparticles. (10th September 2019) - Wang, Dourong; Lu, Jiajia; Luo, Lin; Jing, Shengyu; Abbo, Hanna S.; Titinchi, Salam J.J.; Chen, Zheng; Tsiakaras, Panagiotis; Yin, Shibin
Abstract: Exploring low-cost and high-performance electrocatalysts for hydrogen evolution reaction (HER) still remains a challenging issue. An efficient strategy to enhance HER activity concerns with designing suitable substrates for constructing composite materials. Herein, a new hybrid electrocatalyst, consisting of FeP (iron phosphide) nanoparticles (NPs) anchored on 3D structured graphene (3DG) is investigated towards HER. 3DG substrates are pretreated by an intermittent microwave heating (IMH) method, following the procedure 5s-ON/5s-OFF, repeated for different times. It is found that the as resulted 3DG20 substrate (submitted to 20 repetitions), is favorable for the uniform dispersion of FeP nanoparticles, which presents large specific surface area, abundant oxygen functional groups and easy electron and mass transfer. The as-prepared FeP/3DG20 electrocatalyst displays good HER activity and stability, requiring relatively small overpotentials of −113.2 and −211.4 mV to deliver current densities of −10 and −200 mA cm −2 in 0.5 M H2 SO4 aqueous solution, the corresponding mechanism is discussed. Thus, this study might provide a prospective strategy to enhance HER catalytic efficiency by exploiting the synergy between electrocatalysts and support materials. Graphical abstract: Image 1 Highlights: 3D structured graphene (3DG) is functionalized by a simple intermittent microwave heating method. The resulted 3DG20 with abundant mesoporous morphology facilitates electron and mass transfer. As-prepared FeP/3DG20 exhibits good hydrogen evolution activity and stability in acid media. It requires small overpotentials of −113.2 and −211.4 mV to deliver current densities of −10 and −200 mA cm −2